The effect of cumulative endurance exercise on leptin and adiponectin and their role as markers to monitor training load - Voss, SC; Nikolovski, Z; Bourdon, PC; Alsayraﬁ, M; Schumacher, YO (Biology of Sport, 2016)
Leptin and adiponectin play an essential role in energy metabolism. Leptin has also been proposed as a marker for monitoring training load. So far, no studies have investigated the variability of these hormones in athletes and how they are regulated during cumulative exercises This study monitored leptin and adiponectin in 15 endurance athletes twice daily in the days before, during and after a 9-day simulated cycling stage race. Adiponectin significantly increased during the race (p=0.001) and recovery periods (p=0.002) when compared to the baseline, while leptin decreased significantly during the race (p<0.0001) and returned to baseline levels during the recovery period. lntra-individual variability was substantially lower than inter-individual variability for both hormones (leptin 34.1 vs. 53.5%, adiponectin 19% vs. 37.2%). With regards to exercise, this study demonstrated that with sufficient, sustained energy expenditure, leptin concentrations can decrease within the first 24 hours. Under the investigated conditions there also appears to be an optimal leptin concentration which ensures stable energy homeostasis, as there was no significant decrease over the subsequent race days. ln healthy endurance athletes the recovery of leptin takes 48-72 hours and may even show a supercompensation- like effect. For adiponectin, significant increases were observed within 5 days of commencing racing, with these elevated values failing to return to baseline levels after 3 days of recovery. Additionally, when using leptin and adiponectin to monitor training loads, establishing individual threshold values improves their sensitivity.